Influence of ripening conditions on Scamorza cheese quality - Sorrentino, E.; Tipaldi, L.; Pannella, G.; La Fianza, G.; Succi, M.; Tremonte, P. (International Journal of Agricultural and Biological Engineering, 2013)
Scamorza is a pasta filata cheese produced in Southern Italy and eaten after a short ripening. The ripening phase is critical in defining the main qualitative features of the Scamorza cheese. The success of this operation is conditioned not only by the process parameters, but also by the characteristics of the ripening room in which different microclimates originate. This work intended to evaluate the influence of the different positions of cheeses within the ripening room on the evolution of their qualitative characteristics during the process of drying/ripening. For this purpose, samples of Scamorza cheese, produced in the Molise Region (Italy), were divided into two batches (C and L) and subjected to ripening for seven days in a thermo thermo-regulated room. The two batches were placed in different points of the room: the batch C in the central area and the batch L in the lateral area. During the ripening, temperature, humidity and air flow were monitored and the Scamorza cheeses were analysed to assess some qualitative characteristics. In a ripening room, the created microclimates are able to influence the quality of the product, as demonstrated by data related to temperature, humidity and air flow. In fact, from the results obtained, some appreciable differences among products from batches C and L were observed for the weight loss, the water activity and the colorimetric indexes. Differences in the behaviour of mesophilic lactic acid bacteria, pH and acidity were also found. The more rapid loss of water, characterizing the batch C, resulted in an evolution of physicochemical, physical and microbiological features, which resulted different from those observed in the samples from the batch L. Therefore, the results obtained in this study point out that, within the ripening room, the formation of different micro-environments is able to strongly influence the definition of the qualitative characteristics of the products placed in it.